Effect of HLA type and hypocomplementaemia on the expression of parvovirus arthritis: one year follow up of an outbreak. Issue 1 (January 1996) - Gendi, N S; Gibson, K; Wordsworth, B P
Abstract : OBJECTIVES--To determine the effect of HLA type and hypocomplementaemia on the duration and severity of joint involvement in parvovirus infection (HPV). METHODS--Forty seven patients were selected on a geographical basis from 83 with proven HPV infection during an outbreak that occurred in Oxfordshire in 1993. They were contacted by questionnaire a year later. Thirty five patients were available for examination and blood sampling. Subjects were typed for HLA-DRB1 alleles and HLA-B27 status. Immunological profiles, including C3 and C4 complement components, were determined. RESULTS--Joint symptoms occurred in all patients. They resolved within a week in 12 patients and persisted beyond one year in 19. On review, none had a picture of rheumatoid arthritis, but three patients had developed carpal tunnel syndrome. Decreased C4 was found in four. The HLA frequencies were similar to those in controls; however, joint symptoms persisted for more than one week in all HLA-DR4 positive patients (p = 0.009). There was no relation between the severity of joint symptoms and either HLA type, or hypocomplementaemia. CONCLUSIONS--Joint symptoms are common in parvovirus infection and the presence of HLA-DR4 may be associated with persistence of joint symptoms beyond one week. This study revealed no evidence of progression to rheumatoid arthritis.